LAS FRACCIONES EN LA RECTA NUMÉRICA. UN EXPERIMENTO DE DISEÑO BASADO EN MODELOS DE LONGITUD - Delgado Valdez, Ivette Anel (2026)
This study investigated the feasibility of a Design Experiment framed in Realistic Mathematics Education with the aim of recognizing the mental objects that students develop when working with fractions in the context of length, specifically on the number line. The analysis presented here is the result of a Hypothetical Learning Path, applied to fifth grade students in a school in Mexico City, which shows favorable results for students to modify their fraction schemes towards multiplicative fractional thinking, which is developed by iterating unit fractions so that they can recognize when a fraction is less than, equal to or greater than the unit of reference. The findings suggest that working with fraction comparison in a measurement context, specifically length, is a viable entry point for work with rational numbers and subsequent more complex mathematical knowledge, e.g. algebra.